Getting bigger, quicker? Gendered socioeconomic trajectories in body mass index across the adult lifecourse: a longitudinal study of 21,403 Australians - Wilson, Andrew; Feng, Xiaoqi (My University, 2015)
Do socioeconomic inequities in body mass index (BMI) widen across the adult lifecourse? BMI data for 29,104 male and 32,454 female person-years aged 15 years and older (21,403 persons in total) were extracted from the Household, Income and Labour Dynamics in Australia between 2006 and 2012. Multilevel linear regression was used to examine age and gender specific trajectories in BMI by quintiles of neighborhood socioeconomic circumstance. Models were adjusted for probable sources of confounding, including couple status, number of children resident, if somebody in the household had been pregnant in the last 12 months, the highest level of education achieved, the average household gross income, and the percentage of time in the last year spent unemployed. Approximately 9.6% of BMI variation was observed between neighborhoods. High neighborhood disadvantage was associated with 2.09 kg/m2 heavier BMI (95%CI 1.82, 2.36). At age 15-24y, socioeconomic inequity in BMI was already evident among men and women especially (22.6 kg/m2 among women in the most affluent areas compared with 25.4 kg/m2 among the most disadvantaged). Among women only, the socioeconomic gap widened from 2.8 kg/m2 at age 15-24y to 3.2 kg/m2 by age 35-44y. Geographical factors may contribute to more rapid weight gain among women living in disadvantaged neighborhoods.
Keywords: Health -- Body size, BMI, Body image; Health and wellbeing; Health; Body size, BMI, Body image; Health and wellbeing